Effects of the FIFA 11+ and a modified warm-up programme on injury prevention and performance improvement among youth male football players - Asgari, M.; Alizadeh, M. H.; Shahrbanian, S.; Nolte, K.; Jaitner, T. (PLOS ONE, 2022)
Introduction The effects of the FIFA11+ programme (the 11+) on ankle and groin injuries and performance have remained questionable. The latter, particularly, has potentially reduced the implementation rate and applicability of the programme. This study aimed to evaluate the mid-to-long-term effects of the 11+ and a modified programme including football-specific exercises on injury prevention and performance improvement. Materials and methods Three teams of the Iranian Youth League (division two) volunteered to participate in this study and were randomly assigned to two intervention groups (F11+; n = 29, M11+; n = 31) and a control group (n = 30). The F11+ followed the FIFA 11+ programme, whereas the M11+ performed modified exercises three times weekly as a warm-up protocol before training and competition through a football season. The control group carried out its routine warm-ups, including joggings, basic football drills, and static stretches, while having no injury prevention approaches. Lower extremity injuries, as well as exposure time for each player, were recorded. The football-specific performance was assessed using the Illinois Agility and Slalom Dribbling tests. ANOVA, Fisher Freeman Halton, and chi-square tests were used to analyze the data. Results Injury incidences differed significantly between groups (p = 0.02, C = 0.40), with M11+ reporting the lowest incidence. Significant differences between the pre- and posttest as well as differences between the groups for development over time were revealed for the Illinois agility and dribbling speed (p=0.01). Both performance tests demonstrated a large time effect, as the effect sizes for time in agility and dribbling speed were 0.74 (CI = [0.66; 0.79]) and 0.86 (CI = [0.79; 0.87]), respectively. The effect size for the interaction can be categorized as medium, with 0.38 (CI = [0.25; 0.49]) for agility and 0.52 (CI = [0.40; 0.61]) for dribbling speed. M11+ showed the largest improvement in both. Discussion Mid-to-long-term application of a structured dynamic warm-up that integrates injury prevention and performance approaches may lower injury incidences and improve youth subelite players` performance. Although additional studies with larger samples are needed to prove the results of the current study, the amateur clubs/teams could integrate such twofold dynamic warm up into their routine training plan and benefit its advantages on injury prevention and performance improvement.